Serum bilirubin levels are positively associated with glycemic variability in women with type 2 diabetes - Kim, Lee Kyung (J Diabetes Investig, 2016)
AIMS/INTRODUCTION: Glycemic variability is known to induce oxidative stress. We investigated the relationships between glycemic variability and serum bilirubin levels, an endogenous anti‐oxidant, in patients with diabetes. MATERIALS AND METHODS: A cross‐sectional study was carried out with 77 patients with type 2 diabetes who had been recruited to two clinical studies from 2008 to 2014. There were no participants with diseases of the pancreas, liver, biliary tract and chronic renal insufficiency. Glycemic variation was calculated by a continuous glucose monitoring system, and correlation analyses were carried out to evaluate their association with bilirubin levels. Multiple linear regression was carried out to identify independent factors influencing bilirubin levels and glycemic variation. RESULTS: Among the participants, 42.3% were men. The mean (standard deviation) age was 61.5 years (10.4 years), body mass index was 24.2 kg/m(2) (2.8 kg/m(2)), diabetes duration was 17.7 years (9.5 years), hemoglobin A(1c) was 60.7 mmol/mol (7.1 mmol/mol; 7.7 [0.7]%) and bilirubin was 11.8 μmol/L (4.10 μmol/L). Serum bilirubin levels were not different according to age, body mass index and hemoglobin A(1c). However, the mean amplitude of glucose excursion was positively associated with bilirubin levels in women (r = 0.588, P < 0.001). After adjustment with duration of diabetes, serum albumin, liver enzymes, and mean glucose, the correlation between bilirubin and mean amplitude of glucose excursion remained significant (r = 0.566, P < 0.001). Multiple linear regression analyses showed that bilirubin was an independent determinant for the mean amplitude of glucose excursion in women. 1,5‐Anhydroglucitol was also associated with bilirubin levels in women. CONCLUSIONS: Bilirubin level within the physiological range might be an independent predictor for glycemic variability in women with type 2 diabetes.